Pengaruh Profitabilitas Dan Likuiditas Terhadap Kebijakan Dividen (Studi Perusahaan Pada Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun (2019-2023) - Rika Kartika (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2024)
This research aims to determine the influence of profitability and liquidity on dividendl policy in a study of companies in the property and real estate sector listed on the Indonesian Stockl Exchange for the period (2019-2023). The method used in this research is the descriptive associative method. Data collection techniques are carried out through secondary data, namely data obtained indirectly by studying documents related to research. Data is taken in the form of published data on thel official website of the Indonesian Stock Exchange.The sampling technique in this research used the purposive sampling method. The population in this studyl was 98 companies and the sample used was 11 companies in the property and real estate sector listed on the Indonesian Stock Exchange for the period (2019-2023). The analytical methods used in this research are descriptive analysis, regression analysis with normality test, multicollinearity test and autocorrelation test, hypothesis testing using the t test and analysis of the coefficient of determination.